Trivial differential equations in spaces L_p, 0 < p< 1 - Popova , L. V. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
A description of the set X_p of all solutions of the trivial Cauchy problem in L_p, 0 < p< 1 is presented. The principal result is Theorem 2, which asserts that X_p is a closed subspace of the p -Banach space H_p of all curves in L_p that satisfy a Hölder condition of order р and emanate from relative to the p -norm, which is equal to the minimal constant in the Hölder condition.